Escalation of Divorce Petitions in Bone Regency: Examining Divorce Cases in the Religious Court Class 1A in Watampone - Darliana, Darliana; Misbahuddin, Misbahuddin; Aidit, Hasyim (Al-Bayyinah, 2023)
The escalation of divorce lawsuits has become a significant problem that must be addressed. The high number of divorce cases is clear evidence that the purpose of marriage is not being achieved. It is urgent to pay attention to the strong reasons for the occurrence of divorce lawsuits, as this can form the basis for policy-making, particularly concerning the concept of a strong bond in marriage. This research aims to understand the indicators of the causes of divorce lawsuits and to investigate the consequences and control of those involved in divorce cases. The study is a qualitative descriptive field research with juridical, normative theological, and sociological approaches. The data management used includes data reduction, data presentation, and drawing conclusions. The data analysis results depict a substantial escalation of divorce lawsuits in The Religious Court Class 1A in Watampone over time, with a higher incidence of divorce lawsuits compared to divorce by talak. The factors influencing divorce lawsuits in the Religious Court include moral factors, causing harm, underage marriage, ongoing disputes, biological defects, lack of harmony, all supported by situations of "inability" and "unwillingness" to fulfill rights and obligations in marriage. Divorce lawsuits have a negative impact on both parties and their descendants. Psychologically, it affects the children and the wife, socially it affects the husband and wife due to their status as widows and widowers, and economically it affects the wife's finances, which were previously supported by the husband.